Analysis of social and economic aspects of management of marine and coastal resources based on EAFM (Ecosystem Approach to Fisheries Management) method in Banda Aceh City. (December 2018) - Miswar, E; Natasya, D; Irham, M; Aprilla, R M; Agustina, S; Affan, J M
Abstract: The study was conducted from January to February 2018 located in Lampulo sub-district of Kuta Alam Banda Aceh, Kampung Jawa, Aceh Province. The method of data retrieval was taken from primary data (interview and questionnaire) and secondary data (from related institution and references). The sampling used was purposive sampling method with 15 respondents. Data analysis used was ordinal-based on liker score 1, 2, 3 to each indicator such as; economic domain, fishery household income (RTP), saving ratio and asset ownership, and social domain which is stakeholder participation, fishery conflict and local knowledge in management of fish resources. The overall average indicator scores are 2. The management of coastal and marine resources ecosystems in Banda Aceh city conducted precisely in Kampung Jawa, Lampulo village. The result showed that economic domain is classified with the acquisition of composite value 53.33, and social domain is classified very well with the composite value of 88.88.